Social networks as a source of information and scientific exploration in university students - Díaz Posligua, Katherin Liceth (2024)
In the digital age, social media platforms have become essential for communication and the exchange of information, as well as their use for entertainment purposes, something very common among university students who are adapting to new forms of searches and consumption. of information. This study aims to analyze the use of social networks as a source of information and exploration by students at the Universidad San Gregorio de Portoviejo (USGP). As part of the methodology, a survey was conducted among students from the different academic areas of the USGP to examine the frequency with which they use platforms such as Facebook, Instagram, TikTok, X and WhatsApp to access scientific content. In addition, a bibliographic review was carried out in order to deepen the thematic analysis.  The findings allowed us to understand the role in the evolution of social networks as part of university education, which provide information about the benefits and challenges that these platforms pose in the search for academic knowledge. It is concluded that a majority percentage of university students consider that social networks are not a reliable source of scientific search, while others investigate them a little more by calculating content generated by experts or recognized institutions that enjoy reliability.